The effects of an interdisciplinary supportive educational program on anxiety among patients undergoing cataract surgery - Azam Moladoost; Ali Salehi; Sedigheh Farzi; Akram Dehghani; Hassan Razmjoo; Zahra Soltani Mohammadi; Saba Farzi (Kashan University of Medical Sciences, 2021)
Background: In most ophthalmic surgeries, patients are conscious or semi-conscious, and hence, they may experience varying levels of anxiety during surgery. Objectives: The aim of this study was to evaluate the effects of an interdisciplinary supportive educational program on anxiety among patients undergoing cataract surgery (CS). Methods: This quasi-experimental study was carried out in February-August 2019 using a two-group pretest-posttest design. Participants were 64 patients with cataract who were referred to Feiz Hospital, Isfahan, Iran, for undergoing CS. They were consecutively recruited and randomly assigned to either a control or an intervention group. Data were collected using a demographic questionnaire and Spielberger State-Trait Anxiety Inventory. Participants in the intervention group received an interdisciplinary supportive educational intervention, while their counterparts in the control group received routine care services. State anxiety and trait anxiety were assessed both on the sampling day and after regaining full postoperative consciousness. Data analysis was done via the independent and the paired samples t-, the Mann-Whitney U-, and the Chi-square tests. Results: There were no statistically significant differences between the intervention and the control groups respecting the pretest mean scores of state anxiety (35.25 ± 8.51 vs. 35.72 ± 9.43; P = 0.83) and trait anxiety (38.25 ± 7.002 vs. 39.16 ± 8.58; P = 0.64). However, there were statistically significant differences between the groups regarding the posttest mean scores of state anxiety (28.66 ± 10.39 vs. 34.84 ± 9.36; P = 0.02) and trait anxiety (31.76 ± 8.51 vs. 38.13 ± 10.29; P = 0.01). Conclusion: As a simple and inexpensive intervention, an interdisciplinary supportive and educational program through both face-to-face communication and telecommunication methods is effective in significantly reducing anxiety among patients undergoing CS.